The sensation seeking scale (SSS-V) and its use in Latin American adolescents: Alcohol consumption pattern as an external criterion for its validation - Schmidt, Vanina Ines (2017)
Sensation Seeking is a trait defined by the seeking of varied, novel, complex, and intense situations and experiences, and the willingness to take physical, social, and financial risks for the sake of such experience. The Sensation Seeking Scale (SSS-V) is the most widely used measure to assess this construct. In previous studies a variety of psychometric limitations were found when using the SSS-V with Latin American population. The purpose of this study is to present additional psychometric properties for its use with Latin American adolescents. It was applied to a 506 adolescent sample (from 12 to 20 years). The result is a scale of 22 items that cover four factors. It seems that sensation seeking among Latin American adolescents can be described in terms of four factors, but with some slightly content differences from what is usually found in adult samples from other countries. Future lines of research are proposed.